Role of TcPARP during the metacyclogenesis of Trypanosoma cruzi - Svagzdys, Ailin (2020)
Poly(ADP-ribosyl)ation is a post-translational modification catalyzed by poly(ADP- ribose)polymerases (PARPs). As a reversible modification, it is regulated by a delicate balance ofsynthesis and degradation, and is involved in various nuclear processes related to DNAmetabolism. To adapt to its complex life cycle, T. cruzi undergoes several differentiationprocesses such as metacyclogenesis, where the replicative epimastigote transforms into theinfective trypomastigote. Here we evaluated the role of TcPARP during T. cruzi metacyclogenesisusing Olaparib, a specific PARP inhibitor, with two differentiation techniques: TAU medium andblood agar. Our results using two different T. cruzi strains show that, depending on thedifferentiation technique used, the inhibition of TcPARP stimulates or hinders metacyclogenesis.We also compared the formation of reactive oxygen species (ROS) and autophagosomes duringthe induction of metacyclogenesis on blood agar, in order to understand the pathways that arebeing triggered in this process. Preliminary results indicate that while ROS formation could betriggering the metacyclogenesis in blood agar, autophagy would not be involved in this process.In order to further study this process, we are generating TcPARP knockout cell lines that will helpus corroborate our results.